Retorika Populisme Dalam Kontestasi Politik Di Indonesia: Studi Fenomenologi pada Generasi Milenial terhadap Retorika Post-Truth Calon Presiden pada Pemilihan Presiden 2019 - Deha, Daniel (Institute of Social and Political Science Jakarta (Institut Ilmu Sosial dan Ilmu Politik Jakarta - IISIP Jakarta), 2021)
The 2019 Presidential Election is a practical implication of the post-truth populist trends in Indonesia. This study aims to explore the Millennials’ perception on the post-truth rhetorics of presidential candidates in the 2019 Presidential Election. The theory used in this study is the theory of post-truth rhetorics, grounded on phenomenology and the descriptive-qualitative approach. The article finds that there was a rejection of Prabowo’s post-truth populist rhetorics because they were incompatible with Indonesia’s political, social and cultural characters. In the Indonesian political context, rhetorical ability is not a benchmark. The most important thing is the credibility, integrity, and track record of political actors. It was also found that the media tends to eschew Prabowo’s post-truth populist messages. But in principle, there is almost no stark difference among both candidates’ populist rethorics in the election. Both carry identity politics and are affiliated with elites and oligarchs, so the populist politics are contradictory to the candidates.